Pengaruh Aplikasi Digital Kualitas Informasi Akuntansi, dan Pemahaman Akuntansi Terhadap Kinerja Usaha UMKM di Kota Batam - Restri Ningsih; Dian Efriyenti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology encourages MSMEs to improve financial management to enhance business performance. This study aims to analyze the effect of digital accounting applications, accounting information quality and accounting understanding on the business performance of MSMEs in Batam City. This research employs a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 174 culinary MSME owners in Batu Aji and Sagulung Districts, Batam City. The data were analyzed using multiple linear regression analysis. The results indicate that digital accounting applications, accounting information quality, and accounting understanding each have a positive and significant effect on MSME business performance. Simultaneously, these variables also significantly influence MSME business performance in Batam City. These findings suggest that effective use of digital accounting applications supported by high-quality accounting information and adequate accounting understanding can improve efficiency and competitiveness of MSMEs.